1999
DOI: 10.1155/1999/327643
|View full text |Cite
|
Sign up to set email alerts
|

Speech Impairment in a Large Sample of Patients with Parkinson’s Disease

Abstract: This study classified speech impairment in 200 patients with Parkinson's disease (PD) into five levels of overall severity and described the corresponding type (voice, articulation, fluency) and extent (rated on a five-point scale) of impairment for each level. From two-minute conversational speech samples, parameters of voice, fluency and articulation were assessed by two trained-raters. Voice was found to be the leading deficit, most frequently affected and impaired to a greater extent than other features in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
313
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 521 publications
(339 citation statements)
references
References 16 publications
7
313
1
7
Order By: Relevance
“…Voice and speech deficits are common complications of PD [22][23][24][25][26] and include decreased vocal loudness, decreased frequency variability (monotone), breathiness, hoarse voice quality and imprecise articulation [22,23], as well as degradation in speech intelligibility [27]. Similar to animal models of therapy, targeted exercise (speech/voice therapy) has been shown to improve specific deficits, such as communication and quality of life in patients with PD [28][29][30].…”
Section: Voice and Speech Deficits And Targeted Sensorimotor Trainingmentioning
confidence: 99%
“…Voice and speech deficits are common complications of PD [22][23][24][25][26] and include decreased vocal loudness, decreased frequency variability (monotone), breathiness, hoarse voice quality and imprecise articulation [22,23], as well as degradation in speech intelligibility [27]. Similar to animal models of therapy, targeted exercise (speech/voice therapy) has been shown to improve specific deficits, such as communication and quality of life in patients with PD [28][29][30].…”
Section: Voice and Speech Deficits And Targeted Sensorimotor Trainingmentioning
confidence: 99%
“…These variations in voice patterns become worse as the disease progresses [35]. Research has shown that speech may be a useful signal for discriminating PWP from healthy individuals [37]. On the basis of clinical evidences which suggests that the vast majority of PWP typically exhibit some form of vocal disorder [38] and these vocal impairments are among the earlier PD symptoms preceding the actual Parkinson's disease., even five years prior to clinical diagnosis [39], we can reinforce the fact that voice may reflect disease status.…”
Section: Vocal Impairment In People With Parkinson's (Pwp)mentioning
confidence: 99%
“…Almost 90% of patients have problems related to oral communication (3) , but the voice is affected more quickly and more often than other subsystems (4) and can be the initial symptom. One-third of patients suffers from dysphonia and presents hoarseness and breathy voice as the most impacting deficit (5) .…”
Section: Introductionmentioning
confidence: 99%